The Role of Leadership in Improving the Performance of Lahat Regency Public Works and Public Housing Department Employees: Peran Kepemimpinan dalam Meningkatkan Kinerja Pegawai Dinas Pekerjaan Umum dan Perumahan Rakyat Kabupaten Lahat - Amaludin, Amaludin; Saparudin, Saparudin; Andayani, Melia (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to identify the role of leadership in improving employee performance at the Public Works and Public Housing (PUPR) Department of Lahat Regency. The research method involves interviews with key informants in the organization. The interview results revealed that effective leadership has a significant impact on three main aspects: organizational culture, employee motivation, and work environment. These findings are supported by a recent literature review. This research shows that leadership plays an important role in forming an organizational culture that supports employee performance. Effective leaders are able to promote values that create an environment where employees feel motivated, have a sense of trust, and are ready to contribute optimally. In the context of government organizations, transformational leadership, leader support, and constructive feedback are key factors that influence employee performance. In conclusion, this research confirms the importance of the role of leadership in improving employee performance at the Lahat Regency PUPR Service. To achieve optimal performance, organizations need to invest in effective leadership development and promote a supportive organizational culture. The practical implication is that effective leadership is the key to achieving organizational goals and maximizing human resource potential. Keywords: Leadership, Employee Performance, PUPR Service